Supraventricular arrhythmia in pregnancy. Issue 21 (27th January 2022) - Ramlakhan, Karishma P; Kauling, Robert M; Schenkelaars, Nicole; Segers, Dolf; Yap, Sing-Chien; Post, Martijn C; Cornette, Jérôme; Roos-Hesselink, Jolien W
Abstract : The physiological changes during pregnancy predispose a woman for the development of new-onset or recurrent arrhythmia. Supraventricular arrhythmia is the most common form of arrhythmia during pregnancy and, although often benign in nature, can be concerning. We describe three complex cases of supraventricular arrhythmia during pregnancy and review the currently available literature on the subject. In pregnancies complicated by arrhythmia, a plan for follow-up and both maternal and fetal monitoring during pregnancy, delivery and post partum should be made in a multidisciplinary team. Diagnostic modalities should be used as in non-pregnant women if there is an indication. All antiarrhythmic drugs cross the placenta, but when necessary, medical treatment should be used with consideration to the fetus and the mother's altered pharmacodynamics and kinetics. Electrical cardioversion is safe during pregnancy, and electrophysiological study and catheter ablation can be performed in selected patients, preferably with zero-fluoroscopy technique. Sometimes, delivering the fetus (if viable) is the best therapeutic option. In this review, we provide a framework for the workup and clinical management of supraventricular arrhythmias in pregnant women, including cardiac, obstetric and neonatal perspectives.